Energy efficiency in green building materials application for low-energy indoor eco-friendly / Anas Zafirol Abdullah Halim, Mohd Fareh Majid and Muhammad Naim Mahyuddin - Abdullah Halim, Anas Zafirol; Majid, Mohd Fareh; Mahyuddin, Muhammad Naim (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
World environment climate has changed toward unpredictable weather where average global temperature has increased up to 0.74oC since 1906 until 2005 [1]. This increment is an indication of more heat from the sun is penetrated to our primary protector which is the ozone layer. Due to this scenario, the secondary protector in the forms of the buildings should play major roles in giving comfort to the human. This is where the thermal conductivity of the building material becomes an important matter to study. Thermal conductivity or k-value of solid material describes the ability of heat being transferred through conduction. High k-value describes the material as highly conductive from one point to another. In other words, high k-value material easily allows the heat transfer to pass through it, as such indicating that this is not a good property for building material. The design thickness is very crucial where it will impact the cost of producing green materials. Thicker brick uses more amount of material and hence, it increases the production cost. The requirement on heat resistivity is very important for a building to prevent the building to be hot and uncomfortable. Unlike the clay brick wall and concrete wall, the U-value for green material wall is very low and it can block the entry of large amounts of heat and thereby cooling the building